Angiogenesis in Health and Disease: Role of Vascular Endothelial Growth Factor (VEGF) - Ensieh Salehi; Fateme Sadat Amjadi; Majid Khazaei (مجله دانشکده پزشکی اصفهان, 2011)
Background: Angiogenesis is the formation of new blood vessels from pre-existing ones. It contributes to physiological and pathophysiological conditions. Pathophysiological angiogenesis is associated with several long-term complications of disease such as diabetic retinopathy and nephropathy, endometriosis, hypertension and tumor development while physiological angiogenesis is involved in wound healing, ovulation and menstrual cycles. The process of angiogenesis depends on the balance of many stimulating or inhibiting factors. The key factor that regulates proliferation and migration of endothelial cells is the Vascular Endothelial Growth Factor (VEGF). Angiogenic therapy includes inhibition of abnormal angiogenesis in some conditions such as tumors or diabetes and stimulation of angiogenesis in conditions of ischemia, such as in ischemic heart disease or peripheral vascular disease. In this review, the mechanism of angiogenesis and role of VEGF during physiological and pathological conditions will be reviewed. Keywords: